Turner syndrome-omphalocele association: Incidence, karyotype, phenotype and fetal outcome - Bedei, Ivonne; Gloning, Karl-Philipp; Joyeux, Luc; Meyer-Wittkopf, Matthias; Willner, Daria; Krapp, Martin; Scharf, Alexander; Degenhardt, Jan; Heling, Kai-Sven; Kozlowski, Peter; Trautmann, Kathrin; Jahns, Kai M.; et al. (My University, 2023)
Objective: Omphalocele is known to be associated with genetic anomalies like trisomy 13, 18 and Beckwith–Wiedemann syndrome, but not with Turner syndrome (TS). Our aim was to assess the incidence of omphalocele in fetuses with TS, the phenotype of this association with other anomalies, their karyotype, and the fetal outcomes. Method: Retrospective multicenter study of fetuses with confirmed diagnosis of TS. Data were extracted from a detailed questionnaire sent to specialists in prenatal ultrasound. Results: 680 fetuses with TS were included in this analysis. Incidence of small omphalocele in fetuses diagnosed ≥12 weeks was 3.1%. Including fetuses diagnosed before 12 weeks, it was 5.1%. 97.1% (34/35) of the affected fetuses had one or more associated anomalies including increased nuchal translucency (≥3 mm) and/or cystic hygroma (94.3%), hydrops/skin edema (71.1%), and cardiac anomalies (40%). The karyotype was 45,X in all fetuses. Fetal outcomes were poor with only 1 fetus born alive. Conclusion: TS with 45,X karyotype but not with X chromosome variants is associated with small omphalocele. Most of these fetuses have associated anomalies and a poor prognosis. Our data suggest an association of TS with omphalocele, which is evident from the first trimester.
Keywords: ddc:610